Adaptation of Social Network Analysis for Facilitating Spatial Diagramming During Architectural Conceptual Design Phase - Hoseini, Ali Ghaffarian (2008)
Designers have difficulty visualizing the end results of the projects during the initial architectural conceptual design phase. This research introduces a computational tool—Social Network Analysis (SNA)—commonly used in the communications field to study relationships between people for solving this visualization problem. The research intent was to affirm whether or not SNA can be utilized as a spatial planning tool during conceptual building design. The author posits that since the nodes and structural relationships between the nodes may have similar architectural characteristics, the tool would enable architects to make changes by moving any spaces on a floor plan while safely maintaining their spatial relationships to other spaces. In this research, the author developed a proof-of-concept model using an available SNA tool to facilitate spatial diagramming visualization during conceptual design phase. This study, tested the use of the SNA tool at four levels. The first level determined whether spatial relationship between functional spaces could be developed (such as the living room must be adjacent to the front entry). The second level was on setting priority values for the different nodes and the linkages. The third level determined whether this study could develop grouping relationships between several functional spaces that have a common characteristic (such as public versus private spaces) on one horizontal plan. The final fourth level determined whether the author could develop multiple layers (such as multi floors) that are connected by one common connector (such as a staircase in a double-story house). The corresponding models are validated intellectually by visual comparison between the simulated model of this study and another diagramming by (Nooshin, 2001) that was developed manually. The author is most interested in the fourth level because complexity in the spatial diagramming exercises is caused by multi-layered spatial arrangements at the horizontal and vertical planes. This study provided guidelines in developing a prototype for a spatial diagramming tool, which architects can use to resolve visualization problems when conducting the architectural spatial diagramming.